Using farm typology to understand banana Xanthomonas wilt management in Rwanda - Kabirigi, M.; Hermans, F.; Sun, Z.; Gaidashova, S.V.; McCampbell, M.; Adewopo, J.B.; Schut, M. (Informa UK Limited, 2024)
This study aims to contribute to the understanding of diversity within the context of banana farming and its implications for the management of banana Xanthomonas wilt (BXW) disease in Rwanda. We used a structured questionnaire to collect data from 690 banana farmers in eight districts, representing various agroecological zones, across Rwanda. We implemented principal component analysis (PCA) and hierarchical cluster analysis (HCA) of the data leading to the delineation of three distinct groups of banana farmers, namely: 1) Beer banana farmers (39.1%), 2) Livestock-based farmers (31.7%), and 3) Cooking banana farmers (29.1%). These farm types exhibit apparent differences in their main farming objectives and adoption of BXW management practices. Cooking banana farmers prioritize BXW prevention over control, whereas beer banana farmers exhibit the opposite trend. Livestock-based farmers show no significant difference in practices in comparison to cooking banana farmers. Beer banana farmers predominantly adopt the officially recommended complete mat uprooting (CMU) approach for disease control, while cooking banana farmers adopt the single diseased stem removal (SDSR) method. These findings provide insights for designing customized and targeted interventions to address BXW management effectively, based on farmer typology.